DiaPep277® Shows Promise as a Therapeutic Strategy for Type 1 Diabetes - Vinall, Maria (MD Conference Express, 2012)
Administration of DiaPep277® is safe and represents a promising therapeutic strategy in patients with recent-onset type 1 diabetes (T1DM). Results of two large Phase 3 trials will determine if this therapy might change the current approach to treating newly diagnosed T1DM patients [Tuccinardi D et al. Expert Opin Biol Ther 2011].